Evaluation of life satisfaction index of the elderly people living in nursing homes - (:unkn) unknown (ELSEVIER IRELAND LTD, 2005)
The aim of our study was to evaluate the quality of life of the elderly living in nursing homes. A pool of 183 elderly people living in nursing homes were involved in the study. Data regarding the socio-demographic characteristics and life satisfaction index-A (LSI-A) of the participants were collected by means of a questionnaire during face-to-face interviews. The average LSI-A score of the whole group of participants was 25.26 +/- 5.51. When the mean LSI-A score of participants in relation to their independent variables was analyzed, no statistically significant differences were found for gender, socio-economic status or body mass indexes (BMI). However, the mean LSI-A score of those elderly people who spent some time in leisure activities was significantly higher than those who did not (p = 0.03). In the stepwise linear regression analysis, the education level and place of residence were found to be the statistically significant independent predictors of LSI-A scores in the study group (p = 0.05, p = 0.001). (c) 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: life satisfaction index-A; nursing homes; leisure activities in older ages; QUALITY-OF-LIFE; GERIATRIC REHABILITATION; FUNCTIONAL STATUS; PERFORMANCE